2004
DOI: 10.1109/tpwrd.2004.825127
|View full text |Cite
|
Sign up to set email alerts
|

Var Compensation by Evolutionary Programming Considering Harmonics

Abstract: Modern distribution systems employ several power electronic devices. These inject substantial harmonic content into the power lines. This letter proposes a simple technique for computing the optimal values of capacitor and/or inductor banks to be switched in to minimize the line losses. The method uses an evolutionary programming technique. A simple numerical example is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…2 shows the graphical representation of the analysis of the problem approaches considered by the authors and 'voltage regulation' is the most considered objective function. From the review papers analyzed it can be confirmed that only few of them taken harmonic mitigation into consideration, but it is easy to justify that in some of the other papers this parameter is taken as a desired objective in the power management, specifically when controlling devices incorporated related to power converters, which injects a huge amount of frequency mismatch to the grid that should be considered during this sort of analysis [7,8].…”
Section: Analysis Of the Parameters And Approaches Considered As mentioning
confidence: 99%
“…2 shows the graphical representation of the analysis of the problem approaches considered by the authors and 'voltage regulation' is the most considered objective function. From the review papers analyzed it can be confirmed that only few of them taken harmonic mitigation into consideration, but it is easy to justify that in some of the other papers this parameter is taken as a desired objective in the power management, specifically when controlling devices incorporated related to power converters, which injects a huge amount of frequency mismatch to the grid that should be considered during this sort of analysis [7,8].…”
Section: Analysis Of the Parameters And Approaches Considered As mentioning
confidence: 99%
“…Scientific articles analyzed: [ 6 , 7 , 10 , 23 , 27 , 29 , 30 , 37 , 38 , 39 , 40 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Main Textunclassified
“…However, it does not analyze all the variables nor the compensation through compensating devices; compensation is raised from distributed resources. From the selected articles, it can be evidenced that only one of analyzed papers takes into account the harmonic mitigation, but it is important to clarify that in many other articles this variable is considered as an objective function in the reactive power compensation, mainly through compensation devices based on power electronics, which introduce a large amount of harmonic component to the grid that must be taken into account for this type of global analysis [ 62 , 99 ].…”
Section: Main Textmentioning
confidence: 99%